2017
DOI: 10.1597/15-327
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interferon Regulatory Factor 6 Mutation in an Asian Family with Van der Woude Syndrome

Abstract: Van der Woude syndrome (VWS) is a rare autosomal dominant genetic disorder characterized by orofacial clefting and lip pits. Mutations in the transcription factor interferon regulatory factor 6 gene (IRF6) have been identified in individuals with VWS. We performed direct sequencing of the gene for molecular investigation of a proband with Bangladeshi-Malay ancestry. A novel transition mutation (c.113T>C), which resulted in an amino acid substitution (p.Ile38Thr) in the deoxyribonucleic acid-binding domain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The main cause of lip pits present in VWS is thought to be notching of the lip with fixation of the tissue at the base of the notch or failure of a complete union of the embryonic lateral sulci of the lip, at an early stage of the labial development (Deshmukh et al, ; Ural, Bilgen, Cakmakli, & Bekerecioglu, ). The phenotypes of both lip pits and CL/P show variable forms, even in the same family the manifestations of the patients are different though they carry the same mutation in IRF6 , which is in accordance with previous studies (Butali et al, ; de Lima et al, ; Tan, Lim, Lim, & Lee, ), and the reason may be epigenetic modification of DNA in IRF6 . By comparing the phenotypes and genotypes among the six VWS families, we observed that the type of mutation has no correlation in predicting the severity of this disease, which was similarly described in a previous study (Butali et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…The main cause of lip pits present in VWS is thought to be notching of the lip with fixation of the tissue at the base of the notch or failure of a complete union of the embryonic lateral sulci of the lip, at an early stage of the labial development (Deshmukh et al, ; Ural, Bilgen, Cakmakli, & Bekerecioglu, ). The phenotypes of both lip pits and CL/P show variable forms, even in the same family the manifestations of the patients are different though they carry the same mutation in IRF6 , which is in accordance with previous studies (Butali et al, ; de Lima et al, ; Tan, Lim, Lim, & Lee, ), and the reason may be epigenetic modification of DNA in IRF6 . By comparing the phenotypes and genotypes among the six VWS families, we observed that the type of mutation has no correlation in predicting the severity of this disease, which was similarly described in a previous study (Butali et al, ).…”
Section: Discussionsupporting
confidence: 90%